2005
DOI: 10.1021/ie050517p
|View full text |Cite
|
Sign up to set email alerts
|

Methane Reforming with Carbon Dioxide. The Behavior of Pd/α-Al2O3 and Pd−CeOx/α-Al2O3 Catalysts

Abstract: The catalytic reforming of methane with carbon dioxide on Pd (∼1%)/R-Al 2 O 3 and Pd (∼1%)-CeO x /R-Al 2 O 3 catalysts was studied at 627 °C using a stoichiometric feed mixture. Characterization of fresh and used samples was carried out by TEM and TG analyses. Preliminary experiments in the 600-730 °C temperature range demonstrated that, on Pd/R-Al 2 O 3 , the conversion of CO 2 was larger than that of CH 4 because of the reverse water-gas shift (RWGS) reaction, although the CO/H 2 ratio was close to 1. This b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Addition of MgO notably influences surface properties of the catalyst, including thermal stability of Pd oxides, metallic surface dispersion and particle size, metal sintering and carbon resistances. These surface properties could essentially account for the catalytic performance of the catalysts [8,[14][15][16][17][18][19][20][21][22]62,63]. The XRD results identified that MgO mainly exist as amorphous type on catalysts with Mg loading no more than 7 wt%.…”
Section: Effects Of Additive Mgo On Catalytic Performance Of Pd Catalmentioning
confidence: 96%
See 3 more Smart Citations
“…Addition of MgO notably influences surface properties of the catalyst, including thermal stability of Pd oxides, metallic surface dispersion and particle size, metal sintering and carbon resistances. These surface properties could essentially account for the catalytic performance of the catalysts [8,[14][15][16][17][18][19][20][21][22]62,63]. The XRD results identified that MgO mainly exist as amorphous type on catalysts with Mg loading no more than 7 wt%.…”
Section: Effects Of Additive Mgo On Catalytic Performance Of Pd Catalmentioning
confidence: 96%
“…One of the effective ways is to introduce a second metal to the catalysts. Addition of Ce to Pd/␣Al 2 O 3 distinctly increased activity and stability of catalyst at 627 • C due to suppressing carbon deposition and decreasing Pd sintering [18]. Alkaline earth and rare earth metals (Ba and La) were also found to improve the catalytic stability of Pd/Al 2 O 3 in carbon dioxide reforming of methane at 750 • C [21], which was ascribed to the decrease of the deposited coke amount.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Supported noble metals have promising high catalytic performances and low sensitivities to carbon deposition during the reforming process. In the literature it is found that the supported Pt [3][4][5][6], Rh [7,8] and Pd [9] catalysts are active and stable for this reaction. However, it is important, by the low availability and high cost, to develop active catalysts with very low noble metal content.…”
Section: Introductionmentioning
confidence: 95%